PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL, KEPEMIMPINAN TRANSAKSIONAL, DAN KEPEMIMPINAN DIGITAL TERHADAP KINERJA KARYAWAN - Fina Annisatul Mualifah; Ahmad Mardalis (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
This study aims to analyze the influence of organizational culture, transformational leadership, transactional leadership, and digital leadership on employee performance. The research method used in this research is quantitative method. The sampling technique in this study is probability sampling technique with saturated sample method, data obtained from primary data distributed through closed questionnaires with the help of google from using a Likret scale. Primary data is obtained directly from respondents by providing questionnaires to obtain data on organizational culture, transformational leadership style, transactional leadership, digital leadership and employee performance. The population in this study were 33 Lazizmu employees. The PLS-SEM Analysis technique is used as a tool to predict and explore complex models with less stringent requirements on the data. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The results of this study indicate that organizational culture has no effect on employee performance, but transformational leadership, transactional leadership, and digital leadership affect employee performance.